The Amphiregulin/EGFR axis protects from lupus nephritis via downregulation of pathogenic CD4+ T helper cell responses. Issue 129 (May 2022) - Melderis, Simon; Warkotsch, Matthias T.; Dang, Julien; Hagenstein, Julia; Ehnold, Laura-Isabell; Herrnstadt, Georg R.; Niehus, Christoph B.; Feindt, Frederic C.; Kylies, Dominik; Puelles, Victor G.; Berasain, Carmen; Avila, Matias A.; et al.
Abstract: Systemic lupus erythematosus (SLE) is a common autoimmune disorder with a complex and poorly understood immuno-pathogenesis. Lupus nephritis (LN) is a frequent and difficult to treat complication, which causes high morbidity and mortality. The multifunctional cytokine amphiregulin (AREG) has been implicated in SLE pathogenesis, but its function in LN currently remains unknown. We thus studied the model of pristane-induced LN and found increasing renal and systemic AREG expression during the course of disease. Importantly, renal injury was significantly aggravated in the absence of AREG, revealing a net anti-inflammatory role. Analyses of immune responses showed dual effects. On the one hand, AREG enhanced activation of pro-inflammatory myeloid cells, which however did not play a major role for the course of LN. More importantly, on the other hand, AREG strongly suppressed pathogenic cytokine production by T helper effector cells. This effect was more general in nature and could be reproduced in response to antigen immunization. Since AREG has been postulated to downregulate T cell responses via enhancing Treg suppressive capacity, we followed up on this aspect. Interestingly, however, in vitro studies revealed potential direct and Treg independent effects of AREG on T helper effector cells. In favor of this notion, we found significantly enhanced T cell responses and consecutive aggravation of LN, only if epidermal growth factor receptor (EGFR) signaling was abrogated in total T cells, but not if the EGFR was absent on Tregs alone. Finally, we also found enhanced AREG expression in plasma and renal biopsies of patients with LN, supporting the relevance of our findings for human disease. In summary, our data identify AREG as an anti-inflammatory mediator of LN via broad downregulation of pathogenic T cell immunity. These findings further highlight the AREG/EGFR axis as a potential therapeutic target. Highlights: Amphiregulin (AREG) is overexpressed in murine and human lupus nephritis (LN). AREG activates pro-inflammatory monocytes/macrophages. AREG potently downregulates pathogenic CD4 + T cell responses. The resulting sum effect of AREG in LN is anti-inflammatory and reno-protective. AREG's effects are partly mediated via direct and Treg independent interaction with T helper effector cells.